Successful use of the nocturnal urine alarm for diurnal enuresis. - Friman, P C (1995)
We report the effects of using a urine alarm, typically employed for nocturnal enuresis, to treat chronic diurnal enuresis in a 15-year-old female resident at Boys' Town. The results of an ABAB reversal design indicate that the alarm eliminated wetting in both treatment phases and that continence was maintained at 3- and 6-month follow-up.